2004
DOI: 10.1152/ajplung.00312.2003
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II stimulates nitric oxide production in pulmonary artery endothelium via the type 2 receptor

Abstract: / ajplung.00312.2003.-We previously reported that angiotensin II stimulates an increase in nitric oxide production in pulmonary artery endothelial cells. The aims of this study were to determine which receptor subtype mediates the angiotensin II-dependent increase in nitric oxide production and to investigate the roles of the angiotensin type 1 and type 2 receptors in modulating angiotensin II-dependent vasoconstriction in pulmonary arteries. Pulmonary artery endothelial cells express both angiotensin II type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
35
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 49 publications
6
35
0
Order By: Relevance
“…Recent reports indicate the presence of AT2R in coronary and pulmonary endothelial cells. 34,35 Also, aldosterone actions on human endothelial cells has been demonstrated, 36 making the endothelium another potential target of aldosterone-regulated AT2R expression.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports indicate the presence of AT2R in coronary and pulmonary endothelial cells. 34,35 Also, aldosterone actions on human endothelial cells has been demonstrated, 36 making the endothelium another potential target of aldosterone-regulated AT2R expression.…”
Section: Discussionmentioning
confidence: 99%
“…Aortic banding seems to induce up-regulation of the AT 2 receptor through increased circulating ANG II via the AT 1 receptor, thereby activating a vasodilatory pathway in vessels through the AT 2 receptor via the kinin/NO/cyclic GMP system. Olson et al (2004) found that ANG II stimulated an increase in NOS mRNA, protein expression, and NO production via AT 2 receptors, whereas signaling via the AT 1 receptor negatively regulated NO production in pulmonary endothelial cells. According to Zhao et al (2005), ANG II stimulates an increase in NOS mRNA levels, eNOS protein expression, and NO production via the AT 2 receptor, whereas ANG II seems to down-regulate eNOS protein expression via an AT 1 receptor-linked pathway involving the G ␣ q protein/phosphatidylinositol phospholipase C/Ca 2ϩ /protein kinase C-␣ signaling pathway in bovine pulmonary artery endothelial cells.…”
Section: Angiotensin-induced Endothelium-derived Relaxing Factomentioning
confidence: 95%
“…These results suggest that the relaxing factor induced by Ang II might be NO. NO production by AT 2 receptor activation on endothelial cells has also been reported in canine coronary arteries (Seyedi et al, 1995), rat aorta (Gohlke et al, 1998;Pueyo et al, 1998), rat skeletal muscle microcirculation (Nora et al, 1998), and porcine and rat pulmonary arteries (Hill-Kapturczak et al, 1999;Olson et al, 2004).…”
Section: Discussionmentioning
confidence: 86%